Vote Buying or (Political) Business (Cycles) as Usual? - Aidt, Toke; Asatryan, Zareh; Badalyan, Lusine; Heinemann, Friedrich (The Review of Economics and Statistics, 2020)
We report robust evidence of a new short-run monetary election cycle: the monthly growth rate of the money supply (M1) around elections is higher than in other months in a sample of low- and middle-income countries. We hypothesize this is related to systemic vote buying. Consistent with this, we find no cycle in authoritarian countries and countries with strong political institutions and a pronounced cycle in elections where international election monitors reported vote buying or in close elections. Using survey data on daily consumer expenditures, we show that within-household consumption of food increases in the days before elections.